NEW POTENTIALITIES OF TOPICAL THERAPY OF SEVERE ATOPIC ECZEMA IN CHILDREN - N.G. Korotkiy; A.A. Tikhomirov; Gamayunov; V.N. Korotkii (Педиатрическая фармакология, 2011)
Increasing effectiveness of topical exposure in atopic dermatitis in children, as well as search for new safe external facilities is one of the urgent problems of modern dermatology. Data concerning the need for inclusion of topical calciumneurin inhibitors in the scheme of topical treatment of atopic dermatitis as for the relief of acute and for long term monitoring of the further course of the disease are proved. Authors evaluated and showed the high clinical efficacy, safety and tolerability of tacrolimus ointment 0.03% in the external treatment of 40 children with atopic dermatitis of moderate and severe degrees in children aged from 2 to 15 years. Key words: atopic eczema, topical therapy, long-term control, tacrolimus ointment, children. (Pediatric pharmacology. — 2011; 8 (6): 96–102).